FRAMEWORK FOR QUALITY OF SERVICE SUPPORT IN UMTS/WIMAX INTEGRATED NETWORKS - OUSTA, FIRAS (2016)
The vision of the Fourth Generation (4G) and beyond networks is an all-IP network. It includes different service providers, multi-mode mobile terminals and different types of radio access technologies such as Global System for Mobile Communication (GSM), Universal Mobile Telecommunication System (UMTS), Long Term Evolution (L TE), Wireless Fidelity (Wi-Fi) and Worldwide lnteroperability for Microwave Access (WiMAX). However, the deployment of 4G and beyond networks has presented various challenges for researchers and service providers.